Trade and Financial Contagion in Currency Crises - Salgado, Ranil (IMF Working Papers; Working Paper, 2000)
This paper investigates empirically the relevance of external, domestic, and financial weaknesses as well as trade and financial linkages in inducing financial crises for a sample of 61 emerging market and industrial countries. A panel probit estimation finds these economic indicators to be significant for emerging market countries during the Mexican, Asian, and Russian crises. In particular, the indicators of vulnerability to international financial spillover (common creditor) and of financial fragility (reserve adequacy) are highly significant and appear to explain the apparent regional concentration of these crises. Exchange rate regimes and capital controls, however, do not seem to matter.